Epistemologi Pendidikan Islam dalam Masyarakat Multikultural: Membangun Toleransi Melalui Pendekatan Integral Bayani-Burhani-Irfani: Membangun Toleransi Melalui Pendekatan Integral Bayani-Burhani-Irfani - Buamona B, Samsudin (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This article aims to analyze how the Islamic epistemological approaches—bayani, burhani, and irfani—can be integrally employed to formulate a tolerant and inclusive Islamic education framework within multicultural societies without falling into value relativism. This qualitative study employs a literature review method, drawing from classical and contemporary works on Islamic epistemology and multicultural education. The findings reveal that bayani provides normative foundations through textual and revelatory sources; burhani fosters critical reasoning based on social reality; while irfani refines spiritual sensitivity and empathy. When integrated methodologically, these three approaches form a comprehensive Islamic educational model that is both value-based and open to dialogue. This integration avoids the pitfalls of epistemological extremism and ethical relativism. An Islamic education based on this integral epistemology offers a new paradigm for transformative, humanistic, and contextual pedagogy amid the complexity of global diversity.